2014
DOI: 10.1097/rli.0000000000000072
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Increase of T1 Signal Intensity of the Dentate Nucleus on Unenhanced Magnetic Resonance Images Is Associated With Cumulative Doses of Intravenously Administered Gadodiamide in Patients With Normal Renal Function, Suggesting Dechelation

Abstract: Our study shows that the increase in the unenhanced T1 signal intensity has a linear relationship with the eMRIn in patients with MS and BM. Indeed, we estimated a linear regression model to fit the progressive increase in T1 signal intensity of the dentate nucleus after multiple enhanced MRI scans. This finding suggests substantial dechelation of gadodiamide in patients with normal renal function, raising further concerns regarding the stability of this agent. Further comparative studies with other gadolinium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
297
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(328 citation statements)
references
References 23 publications
21
297
1
9
Order By: Relevance
“…Gadolinium presence was originally observed in bone [5,6,30] and more recently in the brain [7][8][9][31][32][33][34][35][36][37][38][39] in patients with normal renal function.…”
Section: Gadolinium Storage Conditionmentioning
confidence: 98%
“…Gadolinium presence was originally observed in bone [5,6,30] and more recently in the brain [7][8][9][31][32][33][34][35][36][37][38][39] in patients with normal renal function.…”
Section: Gadolinium Storage Conditionmentioning
confidence: 98%
“…The administered gadolinium remains in the human body for a long time and causes abnormal signal intensity on T1WI (Fig. 4) [106][107][108]. Because of the toxicity of gadolinium, residual gadolinium has been attracting increasing attention [109][110][111][112][113][114][115][116].…”
Section: Gadoliniummentioning
confidence: 99%
“…Different ratios have been used for quantitative measurements including DN-to-pons, DN-to-middle cerebellar peduncle, DN-to-cerebellar white matter, DN-to-CSF, DN-to-corpus callosum genu (CC), GP-to-Th, GP-to-CSF, GP-to-CC, Th-to-CC, and Caudate nucleus-to-CC [1][2][3][4][5][6][7][8][9][17][18][19][20]. In a study with healthy volunteers, T1 SI of DN, pons, GP, white matter, and gray matter were all evaluated and normalized with CSF [21].…”
Section: Quantitative Ratios Measurementsmentioning
confidence: 99%
“…Some authors suggested that 6 or more contrast enhanced MRI were needed to evaluate T1 signal changes over time [1,2], while others evaluate the effect of only one high dose GBCA [21]. Provided that the number of doses were all accounted for, including brain and other contrast enhanced MRI, the critical factor is that only one GBCA should be evaluated for each patient to determine the potential for deposition of each agent.…”
Section: Gbca Related Concernsmentioning
confidence: 99%
See 1 more Smart Citation